PP.25 Interpregnancy Changes in Maternal Weight and Body Mass Index. (26th April 2013) - Crosby, DA; Collins, M; O'Dwyer, V; O'Higgins, A; Farah, N; Turner, MJ
Abstract : Objective: This longitudinal study examined changes in maternal weight and Body Mass Index (BMI) in the early pregnancy between a woman's first and second baby. Methods: We studied women more than 18 years old with a singleton pregnancy who delivered their first baby weighing ≥ 500 grammes in 2009 and who re-attended for antenatal care with a subsequent ongoing pregnancy before January 1st 2012. Maternal weight and height were measured accurately before 18 weeks gestation in both pregnancies and BMI was calculated. Results: Of the 3284 primigravidas, the mean weight at the first antenatal visit was 66.4 kg (SD 12.7). The mean BMI was 24.5 kg/m2 (SD 4.6), and 11.3% (n = 370) were obese. Of these 3284 women, 1220(37.1%) re-attended for antenatal care before 2012 after confirmation of an ongoing pregnancy. Of the 1220 women who re-attended, 788 (64.6%) had gained weight (mean 4.6 kg SD 3.9), 402(33.0%) had lost weight (mean 3.0 kgs SD 2.9) and 30 (2.4%) had maintained their weight. As a result, 20.2% (n = 247) were now in a higher BMI category and 4.8% (n = 58) had become obese; 5.8% (n = 71) were in a lower BMI category and 1.2% (n = 15) were no longer obese. These early pregnancy weight changes were influenced by maternal age, but not by the duration of the interpregnancy interval. Conclusion: As two thirds of women gain weight in the short-term after delivery of their first baby, we recommend that the advice women get before and during pregnancy needs to be reinforced postpartum.